2018
DOI: 10.30638/eemj.2018.300
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Issues. Case Study: The Multipurpose Sports Hall of the University of Oradea

Abstract: The present paper is a multidisciplinary investigation of the indoor air quality inside the Multipurpose Hall of the University of Oradea, based both on specific monitoring and questionnaire-based survey to identify people's perception in this regard. The monitoring, carried out during October-November 2016 when the heating did not work, was focused on: relative air temperature and humidity (Thermohygrometer data logger Klimalogg Pro), carbon dioxide (CO2) (Extech Instruments CO250 model automatic gas analyzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Microbiological contamination and its implications on cultural heritage frescoes were studied by Radu et al [34], Mohanu et al [35], Bucsa and Bucsa [36] and Ilies , et al [37]. Further, other relevant studies focus on the determination of fungal contamination and microclimatic problems in museums [13,[38][39][40][41], sport halls [42,43] or schools [44][45][46]. These studies have shown that among the most common fungi that can be identified in the old wooden churches on the Romanian territory are Aspergillus spp., Mucor spp., Arthrinium spp., Stachybotrys spp., Scopulariopsis spp., Penicillium spp., Absidia spp., Geotrichum spp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Microbiological contamination and its implications on cultural heritage frescoes were studied by Radu et al [34], Mohanu et al [35], Bucsa and Bucsa [36] and Ilies , et al [37]. Further, other relevant studies focus on the determination of fungal contamination and microclimatic problems in museums [13,[38][39][40][41], sport halls [42,43] or schools [44][45][46]. These studies have shown that among the most common fungi that can be identified in the old wooden churches on the Romanian territory are Aspergillus spp., Mucor spp., Arthrinium spp., Stachybotrys spp., Scopulariopsis spp., Penicillium spp., Absidia spp., Geotrichum spp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Classrooms that are too dry can dry out the respiratory tract and room air, which can cause respiratory infections. [16] . In addition, volatile organic compounds are the main cause of dry air because they can cause sensory irritation [17] .…”
Section: Disucussionmentioning
confidence: 99%
“…Another critical parameter involved in the quality of wastewater from the food industry is the high concentration of solid suspensions [7][8][9] (generally characterized by the presence of fats, oils, but also waste resulting from the processing of vegetable raw materials); it is necessary to be separated before the water enters the urban water cycle. At the same time, effluents from the food industry contain significant amounts of nutrients [10] (organic nitrogen or phosphorus) (e.g., effluents from the production of bakery products) [7], but also of heavy metals (copper, chromium, nickel, lead) [11]. Technological processes in the food and beverage industry are the primary sources of wastewater production.…”
Section: Introductionmentioning
confidence: 99%